Response of Millennial Muslims to Religious Minority Groups in Indonesia - Hasse Jubba; Ahmad Sunawari Long; Ririt Yuniar (Al-Albab, 2021)
Religious minority groups have historically been positioned as the trigger for religious and social disharmony. This paper aims to explore the millennial Muslims’ basis for their positioning towards minority groups in Indonesia. The data collected through questionnaires, interviews, and document studies were analyzed and then converted into narrative form, tables, diagrams, and charts. The findings show that there are two millennial Muslim responses towards religious minority groups. First, some are responding with acceptance of non-Islamic affiliated minority groups. Of the 412 surveyed respondents, 280 or 67, 96% stated their acceptance based on the juridical-constitutional reason that every citizen has the same rights and obligations, including the rights to live and obey the law. Representing the second millennial response, most respondents also rejected Islamic-affiliated minority groups. 383 respondents (93%) stated this rejection noting that they believe in the existence of these groups damaging Islam’s image. The different forms of response are based on theological, juridical, and cultural reasons that can be found in religious arguments, legislation, and values of the local wisdom of the Indonesians. This study proposes the need of building better understanding among millennial Muslims regarding social diversity in Indonesia, and finding common ground for these differences that can be applied to avoid religious conflicts in the future.